2002
DOI: 10.1046/j.1365-2524.2002.00389.x
|View full text |Cite
|
Sign up to set email alerts
|

Utilisation of postnatal care in Bangladesh: evidence from a longitudinal study

Abstract: Utilisation of health services is a complex behavioural phenomenon. Empirical studies of preventive and curative services in Bangladesh have often showed that the use of health services is related to the availability, quality and cost of services, as well as to social structure, health beliefs and personal characteristics of the users. The present paper attempts to examine factors associated with the utilisation of healthcare services during the postnatal period in Bangladesh by using prospective data from a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
90
3
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(104 citation statements)
references
References 11 publications
9
90
3
2
Order By: Relevance
“…A study in rural Bangladesh confirmed that higher education was associated with the higher use of ANC. 20 Primary-level of education (p<0.010), secondary level of education (p<.001), living children (p<0.001), read newspaper (p<.024), watching TV (p<0.001), and mode of transport (p<0.001) were the important correlates of ANC during pregnancy of the postnatal mothers.…”
Section: Discussionmentioning
confidence: 96%
“…A study in rural Bangladesh confirmed that higher education was associated with the higher use of ANC. 20 Primary-level of education (p<0.010), secondary level of education (p<.001), living children (p<0.001), read newspaper (p<.024), watching TV (p<0.001), and mode of transport (p<0.001) were the important correlates of ANC during pregnancy of the postnatal mothers.…”
Section: Discussionmentioning
confidence: 96%
“…Over the years the salient functions of ANC have been to offer health information and services which firstly improves the health of women and the new-born [14]. Secondly, receiving ANC during pregnancy has emerged to have a positive effect on the utilization of postnatal healthcare services which reduces the odds of neonatal deaths [15]. The probability for inverse pregnancy outcome gets reduced almost by 90 percent for those having ANC visits four or more.…”
Section: Survey Of Literaturementioning
confidence: 99%
“…11,12 Early booking for antenatal care is also positively associated with four or more visits and such parturient are more likely to be assisted by a skilled attendant at birth. 13,14 Early booking is therefore a strong predictor of positive pregnancy outcome.…”
Section: Introductionmentioning
confidence: 99%
“…3 Several reasons have been adduced for this, including high cost of antenatal care, distance from the health facility, lack of permission from the husband, and cultural perception of health status in pregnancy. [11][12][13][14][15] This study was therefore conducted to determine the time of booking for antenatal care among women in the University of Uyo Teaching Hospital, Uyo, Akwa Ibom State, Nigeria.…”
Section: Introductionmentioning
confidence: 99%